Dual Method Use among Postpartum HIV-Infected and HIV-Uninfected Malawian Women: A Prospective Cohort Study. (18th July 2017) - Kopp, Dawn M.; Tang, Jennifer H.; Stuart, Gretchen S.; Miller, William C.; O'Shea, Michele S.; Hosseinipour, Mina C.; Bonongwe, Phylos; Mwale, Mwawi; Rosenberg, Nora E.
Abstract : Dual method use, use of condoms plus another effective contraceptive method, is important in settings with high rates of unintended pregnancy and HIV infection. We evaluated the association of HIV status with dual method use in a cohort of postpartum women. Women completed baseline surveys in the postpartum ward and telephone surveys about contraceptive use 3, 6, and 12 months later. Nonpregnant women who completed at least one follow-up survey were eligible for this secondary analysis. Prevalence ratios were calculated using generalized estimating equations. Of the 511 sexually active women who completed a follow-up survey, condom use increased from 17.6% to 27.7% and nonbarrier contraceptive use increased from 73.8% to 87.6% from 3 to 12 months after delivery. Dual method use increased from 1.0% to 18.9% at 3 to 12 months after delivery. Dual method use was negligible and comparable between HIV-infected and HIV-uninfected women at 3 months but significantly higher among HIV-infected women at 6 months (APR = 3.9, 95% CI 2.2, 7.1) and 12 months (APR = 2.7, 95% CI 1.7, 4.3). Dual method use was low but largely driven by condom use among HIV-infected women at 6 and 12 months after delivery.